(untitled) (Scientific journal of the Fergana State University, 2023)
This article presents suggestions and comments aimed at improving the role of the mass media in forming the legal consciousness and culture of young people in the society, which is considered to be relevant nowadays. During the research, observation, document study, analysis-synthesis, and statistical analysis methods were used. The research process shows that in order to ensure the stability of the country, it is revealed that there is a need to improve the legal culture of young people. Informing the youth about the issued laws and decisions, it should be focused on the rapid dissemination of information. It was emphasized the need to improve the activities of mass media and develop effective mechanisms for raising the legal consciousness and culture of young people from social networks.